ECHOCARDIOGRAPHIC ABNORMALITIES OF THE MITRAL VALVE ASSOCIATED WITH A LARGE PERICARDIAL EFFUSION - Salem, Bakr I. (1979)
Features of mitral stenosis and systolic anterior motion of the mitral valve were observed on the echocardiogram of a patient with a large posterior pericardial effusion. The abnormal findings disappeared with resolution of the fluid. Because pericardial effusion may result in the echocardiographic alteration of cardiac structures, repeat study is necessary after the effusion has cleared.